2020
DOI: 10.1002/ceat.201900501
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Electrical Conductive Paths within All‐Solid‐State Battery Electrodes

Abstract: All-solid-state batteries constitute a very promising energy storage device. Two very important properties of these battery cells are the ionic and the electrical conductivity, which describe the ion and the electron transport through the electrodes, respectively. In this work, a numerical method is presented to model the electrical conductivity, considering the outcome of discrete-element method simulations and the intrinsic conductivities of both the active material particles and the conductive additive part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…The electrical network conductivity is strongly dependent on the conductive paths from the current collector to the separator. 39 Therefore, it is of interest to evaluate conductivity with respect to these paths. Here, the focus is set on two structural network properties: (I) the number of transit edges χ TP and (II) the transit path length λ TP .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical network conductivity is strongly dependent on the conductive paths from the current collector to the separator. 39 Therefore, it is of interest to evaluate conductivity with respect to these paths. Here, the focus is set on two structural network properties: (I) the number of transit edges χ TP and (II) the transit path length λ TP .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The electrical network conductivity is strongly dependent on the conductive paths from the current collector to the separator . Therefore, it is of interest to evaluate conductivity with respect to these paths.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative approaches, leading to qualitatively similar results were presented previously. 28,29 In the first case, 25 a Hertz−Mindlin type contact law was applied to calculate contact forces between particles, and an empirically derived expression for the resistance between two spheres, normalized to a resistance of a cylinder was used. In the second case, 29 a similar approximation of a sphere to a cylinder was used and a similar assumption of parallel connectivity paths was used as in Figure 3.…”
Section: Methodsmentioning
confidence: 99%
“…3b). Further investigations have also shown that the amount and the particle size of electrolytes, active materials and electron conductors are key for effective contact [34][35][36]. For example, Kimura et al [37] perform operando 3D observations of electrolyte/electrode microstructures using a combination of computed-tomography and X-ray absorption near edge structure spectroscopy and found that higher active material loadings can lead to aggregation and Li-ion and electron transfer pathway reduction.…”
Section: Electrolyte and Electrode Microstructuresmentioning
confidence: 99%